Factors Predicting Mortality in Perforation Peritonitis at a Tertiary Care Center in Nepal - Kansakar, Prasan; Ghimire, Bikal; Mishra, Parashuram (Journal of Institute of Medicine Nepal, 2019)
Introduction Perforation peritonitis is a common surgical emergency. Despite advances in surgical techniques, antimicrobial therapy and intensive care support, mortality due to this illness still remains high. To analyze various demographic and clinical parameters associated with mortality in patients undergoing surgery for hollow viscus perforation peritonitis. Methods A prospective observational study was conducted at the Surgical Gastroenterology Unit, Department of Surgery, Tribhuvan University Teaching Hospital, in patients undergoing surgery for perforation peritonitis over a period of 18 months. Demographic characteristics, physiological variables and laboratory values were obtained. End point of the study was patients’ condition at discharge or in-hospital mortality. Univariate and multivariate analysis of various demographic, clinical and laboratory parameters were performed. Results Among 121 patients, mean age was 41.5±18.9 years (range of 16 to 87 years). There was a male preponderance (74.1%). In-hospital mortality was seen in 19 patients (17.0%). Age, female sex, pulse rate, blood pressure, white blood cell count, urea and creatinine were significant parameters associated with mortality. Multivariate logistic regression analysis of the variables found to be of significance from univariate analysis showed that only pulse, systolic blood pressure and creatinine were the independent variables associated with mortality. Conclusion Higher mortality was seen in elderly patients. Despite of male preponderance, larger proportion of females succumbed to their disease. Derrangement in vital parameters like pulse and blood pressure and renal function test had negative impact in survival.